Efektivitas Metode Pengajaran dalam Meningkatkan Hasil Belajar PAI Siswa SD: Meta-Analisis - Faisol, Muhammad Aris (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to analyze the effectiveness of teaching methods to improve learning outcomes of Islamic education for elementary school students. Of 65 studies available, 20 were collected. The 65 studies were obtained from e-journals, advanced databases such as Google Scholar, DOAJ, ERIC, Springer, Elsevier and Research Gate. Of the 20 studies, the researcher found 41 data artifacts related to the learning outcomes of Islamic education for elementary school students after the implementation of teaching methods and processed using JASP software for meta-analysis. The learning outcomes of Islamic education in this meta-analysis study include students’ mastery of Islamic Education concepts, affective domain, and psychomotor domain. The results showed that the learning outcomes of students' Islamic education were more than cut score (75) because zcount (18.55) <ztable (1.96), which means H0 is accepted and Ha is rejected. It can be concluded that the teaching method is effective in improving students’ learning outcomes. This can be because each study has a different and small sample. Meanwhile, the range of scores reported also varies.